Adenocarcinoma of the Right Breast in a Man with Intellectual Disability - Daniel Satgé; Bernard Leduc; Fernand Raffi; Etienne Roux (Case Reports in Oncological Medicine)
A 64-year-old man with moderate intellectual disability developed a large right breast carcinoma with lymph node metastases. Cancer treatment is often difficult in persons with intellectual disability. However, the patient could be treated according to the current protocols with surgery, chemotherapy, and radiotherapy. He is alive and in good health two years after discovery of his tumor. Although breast cancer is estimated as frequent in women with intellectual disability as it is in nondisabled women, our patient is the second man with intellectual disability reported with a breast carcinoma.